The Effects of Gig Economy Platforms on Job Security and Worker Identity in Indonesian Metropolitan Areas - Hendrian, Sukma (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
The rapid expansion of gig economy platforms has transformed labour markets globally, raising questions about job security and worker identity, particularly in emerging economies with high informality such as Indonesia. Metropolitan areas like Jakarta, Surabaya, Bandung, and Medan have become hubs for ride-hailing, food delivery, and online freelancing, yet workers remain classified as partners rather than employees, exposing them to volatile earnings, limited benefits, and algorithmic control. This study aims to examine the effects of gig economy platforms on job security and worker identity in Indonesian metropolitan contexts. Employing a mixed-methods design, the research surveyed 400 platform workers and conducted 40 semi-structured interviews. Quantitative data were analyzed through descriptive statistics, regression, and structural equation modeling, while qualitative narratives were coded thematically. Validity and reliability were ensured through factor analysis and Cronbach’s alpha, with α ≥ .73. Findings reveal significant income volatility (57% of respondents), limited social protection (28% enrolled in BPJS), and exposure to opaque deactivations (16%). Algorithmic intensity strongly predicts job insecurity (β = 0.31, p < .001), which in turn erodes worker dignity and status. Interviews highlight identity strategies such as entrepreneurial reframing, compliance professionalism, and collective coping, while metropolitan differences—especially in Jabodetabek—intensify precarity due to tariff regulations and congestion. The study contributes to global debates on algorithmic management and identity-work by situating them in Indonesia’s metropolitan labour markets. Practical implications include the need for tariff governance sensitive to urban contexts, portable social benefits, and transparent deactivation procedures to ensure fairer digital labour ecosystems.